1999
DOI: 10.1161/01.atv.19.5.1223
|View full text |Cite
|
Sign up to set email alerts
|

Western-Type Diets Induce Insulin Resistance and Hyperinsulinemia in LDL Receptor-Deficient Mice But Do Not Increase Aortic Atherosclerosis Compared With Normoinsulinemic Mice in Which Similar Plasma Cholesterol Levels Are Achieved by a Fructose-Rich Diet

Abstract: Abstract-The role of insulin resistance (IR) in atherogenesis is poorly understood, in part because of a lack of appropriate animal models. We assumed that fructose-fed LDL receptor-deficient (LDLR Ϫ/Ϫ ) mice might be a model of IR and atherosclerosis because (1) fructose feeding induces hyperinsulinemia and IR in rats; (2) a preliminary experiment showed that fructose feeding markedly increases plasma cholesterol levels in LDLR Ϫ/Ϫ mice; and (3) hypercholesterolemic LDLR Ϫ/Ϫ mice develop extensive atheroscler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
105
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 73 publications
(80 reference statements)
14
105
2
Order By: Relevance
“…However, there was no increase in spontaneous atherosclerosis in the aorta compared with LDLR Ϫ/Ϫ mice on a FD. 35 In addition, compared with the development of insulin resistance, as determined by insulin release profiles in our apoE Ϫ/Ϫ mice fed a FD, the LDLR Ϫ/Ϫ mice did not develop insulin resistance while on a FD. 35 Previous studies in the LDLR Ϫ/Ϫ mice have shown a reduction in lesion formation in male mice treated with thiazolidinediones but not female mice, as we report in our experiments.…”
Section: Phillips Et Almentioning
confidence: 82%
See 1 more Smart Citation
“…However, there was no increase in spontaneous atherosclerosis in the aorta compared with LDLR Ϫ/Ϫ mice on a FD. 35 In addition, compared with the development of insulin resistance, as determined by insulin release profiles in our apoE Ϫ/Ϫ mice fed a FD, the LDLR Ϫ/Ϫ mice did not develop insulin resistance while on a FD. 35 Previous studies in the LDLR Ϫ/Ϫ mice have shown a reduction in lesion formation in male mice treated with thiazolidinediones but not female mice, as we report in our experiments.…”
Section: Phillips Et Almentioning
confidence: 82%
“…35 In addition, compared with the development of insulin resistance, as determined by insulin release profiles in our apoE Ϫ/Ϫ mice fed a FD, the LDLR Ϫ/Ϫ mice did not develop insulin resistance while on a FD. 35 Previous studies in the LDLR Ϫ/Ϫ mice have shown a reduction in lesion formation in male mice treated with thiazolidinediones but not female mice, as we report in our experiments. 25,26 It is important to note that these studies evaluated spontaneous atherosclerosis in the aortic cusp and aorta in contrast to the model of arterial injury and carotid lesion formation in our experiments.…”
Section: Phillips Et Almentioning
confidence: 82%
“…91 Insulin resistance by itself did not alter lesion area. 92 In other studies diabetic LDL receptor knockout mice developed more lesions associated with a marked increase in plasma cholesterol. 58 A recent paper described experiments in which early lesions in chow fed mice were increased with viral destruction of the pancreatic islets.…”
Section: The Apob Transgenics Do Not Normally Develop Diabetes-inducementioning
confidence: 91%
“…When normalized for plasma cholesterol levels, in some studies fructose ingestion is associated with greater lesion development. 92 …”
Section: Are Mice Missing An Enzyme That Mediates the Pathological Efmentioning
confidence: 99%
“…Female mice were used because male mice can develop a type 2 diabetes-like phenotype on high-fat/high-cholesterol diets. 23 Mice were housed in a specific pathogen-free facility with 12-hour light/dark cycles and had free access to food and water. These studies were approved by the Animal Care and Use Committees of the University of Kentucky and the Lexington Veterans Affairs Medical Center.…”
Section: Murine Studies Ldlrmentioning
confidence: 99%